Alstonia scholaris as a Medicinal Plant: Bibliometric Analysis - Husain, Syafia; Ihsan Rizal, Muhammad (Jurnal Kedokteran Gigi Terpadu, 2025)
Background: Alstonia scholaris is a native species in South and Southeast Asia, Australia, and China. This tree has been traditionally used in alternative medicine for centuries, particularly in India and Southeast Asia, to treat various diseases. The leaves, bark, roots, and sap of A. scholaris possess diverse medicinal properties, including antidiabetic, analgesic, anti-inflammatory, antimalarial, antioxidant, anticancer, antimicrobial, and antifungal activities. The presence of phytochemicals contributes to its therapeutic potential. Objectives: The goal of this study was to find and describe the scientific literature on Alstonia scholaris as a medicine plant. Methods: This study conducts a comprehensive literature search on Alstonia scholaris as a medicinal plant, using Scopus as the primary database. The extracted data was filtered, visualized, and analyzed using OpenRefine, VOSviewer, and Scopus Analyzer. Main findings: The visual representation illustrates the interconnectedness of 21,013 related keywords and maps the evolution of keyword usage over time. Publication trends show fluctuating interest over the past 15 years. Contributions from different journals and the leading role of certain authors and institutions underscore the global collaboration in this field, especially among researchers from Asia. Conclusion: These findings underscore the relevance of this plant in pharmacological and medicinal research, particularly highlighting the central role and major contributions from authors and institutions across Asia.